Development of an Android-Based Interactive E-Module Using the Problem-Based Learning Method - Adhita Meizaldi Hartoyo; Nur Qudus; Ulfah Mediaty Arief; Wara Dyah Pita Rengga (Universitas Negeri Semarang, 2026)
The rapid growth of digital technology has created significant opportunities for innovation in educational practices, including the use of Android-based e-modules as self-directed learning media. In the context of Vocational Education, particularly the Motorcycle Engineering expertise program, there is a strong need for interactive learning materials that can enhance the conceptual understanding and cognitive abilities of students. This study aims to develop an Android-based interactive e-module using the Problem-Based Learning (PBL) model for the topic of motorcycle workshop management elements, and to examine its validity, practicality, and effectiveness. The research employed the ADDIE research and development model with participation from media experts, material experts, teachers, and Grade XI TSM students at SMK Cordova Margoyoso. Research instruments included expert validation sheets, practicality questionnaires, and pre-test and post-test assessments. The findings indicate that the e-module is valid, with a media expert validation score of 3.7 (91%) and a material expert score of 3.6 (91%). The e-module was also considered practical based on student evaluations. In addition, it proved effective in improving cognitive abilities, as shown by an N-Gain score of 64% (moderately effective category) and a T-test significance value of 0.000 < 0.05. In conclusion, the Android-based interactive e-module developed using the PBL model meets the criteria of validity, practicality, and effectiveness as a learning medium.